Ratio of Early to Late Type Stars in SMC Clusters - Kontizas, E.; Kontizas, M.; Dapergolas, A.; Hatzidimitriou, D. (1988)
Spectral classification of stars in SMC clusters provide useful information on the evolutionary history of this galaxy and permit to test the theory of stellar evolution.